Expressway Connectivity and Economic Growth: A Case Study of Vietnam - TRAN, Minh Tu; SEYA, Hajime; AOKI, Shunta (Journal of the Eastern Asia Society for Transportation Studies, 2024)
In this study, we estimated the impact of expressway connectivity on economic growth in Vietnam. We developed a novel distance-weighed harmonic centrality and used it along with the conventional degree and harmonic centralities as the indicators of expressway connectivity. Furthermore, we considered one of the following as the outcome for economic growth: population, in-/out-migration rate, registered foreign direct investment (FDI) capital, number of FDI projects, or the number of passengers on the road (“road passenger numbers”). A conventional two-way fixed-effects model was used to estimate the impacts. The results show that improved expressway connectivity is positively associated with higher in-migration rates, FDI capital and projects, and road passenger numbers.